Optimization of the Process of Selection of Software in the Organization - A. Yu. Lukyanenko (Цифровая трансформация, 2020)
The scientific article explores the role of software as a tool used by organizations to carry out economic activities in a digital economy without which it is impossible to have adequate competitiveness in a digital economy. The concept of “digital economy” has been clarified. A methodology has been developed to evaluate the effectiveness of the software used or selected on the basis of its qualitative and quantitative characteristics and the requirements of the workplace for the software functionality. Based on the theoretical and methodological base and the developed methodology, a scalable model of an effective management decision-making process for selecting and updating software in an organization is built, a comparison with existing practice is carried out. The significance of the research results is due to the lack of widely available methods in open access for the optimal selection of software as a tool, not related to involving external agents in the process and having the necessary scalability to use them, including collective, in organizations. This creates negative effects for organizations and the economy of the Republic of Belarus as a whole.